SCREENING AND CHARACTERIZATION OF BACTERIAL CHITOSANASE FROM MARINE ENVIRONMENT - Ekowati Chasanah; Dewi Seswita Zilda; Agustinus R Uria (JOURNAL OF COASTAL DEVELOPMENT, 2009)
Screening of extracellular chitosanase from bacterial isolates associated with marine sponges have been done. Out of 100 bacterial isolates, forty isolates were capable of forming clearing zones on the chitin media and one isolate, 34-b, produced the highest chitinolytic index. The enzymes was produced on chitin liquid medium at 37oC in a shaking waterbath for a five-day cultivation. Crude enzymes were prepared by cell-free supernatant (CFS) and concentrated through 70% (saturated) ammonium sulphate percipitation followed by dialysis. The enzymes worked best at pH and temperature of 6-7 and 60oC, respectively. The half-life (T1/2) for chitosanase activity was 500.2 min or 8.34 hours (at 37oC) and 55.12 min (at 50oC), indicating the enzyme are quite stable at that temperature. However, around 80% of the original activity was lost at 60oC after 15 min of incubation.